2009
DOI: 10.1902/jop.2009.080626
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Wound Healing With and Without Platelet‐Rich Plasma: Histologic Observations and Assessment of Flap Tensile Strength

Abstract: PRP did not seem to contribute to greater flap strength at any post-surgical time point, nor was it associated with any histologic differences in wound healing in this Yucatan minipig model. The time points chosen for observation post-surgery, as well as the variability in the PRP platelet count, may have contributed to the lack of positive findings in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…Therefore, we can conclude that the data obtained so far suggests that PRP is not always effective for periodontal wound healing [68e73], although the variability of PRP preparation, defect size, and surgery procedure may also contribute to the lack of positive findings in those studies. While no substantial evidence supports the routine application of PRP products in daily clinical practice, there is still great interest concerning its use in combination with bone grafts as a potential modality for periodontal regeneration and there do have positive outcomes in several crosssectional investigations [69,71]. For example, the treatment of deep intra-bony periodontal defects with a combination of PRP and bone grafts has led to a significantly favorable clinical and radiographic improvement [73,74].…”
Section: The Use Of Prp In Periodontal Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we can conclude that the data obtained so far suggests that PRP is not always effective for periodontal wound healing [68e73], although the variability of PRP preparation, defect size, and surgery procedure may also contribute to the lack of positive findings in those studies. While no substantial evidence supports the routine application of PRP products in daily clinical practice, there is still great interest concerning its use in combination with bone grafts as a potential modality for periodontal regeneration and there do have positive outcomes in several crosssectional investigations [69,71]. For example, the treatment of deep intra-bony periodontal defects with a combination of PRP and bone grafts has led to a significantly favorable clinical and radiographic improvement [73,74].…”
Section: The Use Of Prp In Periodontal Therapymentioning
confidence: 99%
“…However, published data on PRP-assisted grafting reports variable clinical outcomes, regardless of whether or not the study authors are in support of the PRP concept [69,71,74,75]. Sound biological rationale and a multitude of basic science research supports the use of PRP in promoting soft tissue healing, although evidence of its role in enhancing periodontal applications, especially root coverage, is limited.…”
Section: The Use Of Prp In Periodontal Therapymentioning
confidence: 99%
“…PRP is often used in clinical studies, such as application to periodontal wound healing [6], alveolar bone healing after extraction [4] [12] [13], etc. Dutta, et al reported that they used PRP in empty extraction socket of impacted mandibular third molars, and has significant improvement in soft tissue healing and bone density in extraction sockets [12].…”
Section: Discussionmentioning
confidence: 99%
“…Mariano et al describes that Autologous PRP accelerates alveolar bone generation after tooth extraction [4], while Mooren et al describe that early and late bone healing was not enhanced when PRP was used [5]. At the point of oral mucosa, Powell et al told that PRP did not enhance gingival wound healing as measured by flap strength, nor did it alter the histologic appearance of the tissue compared to sites not treated with PRP [6]. The purpose of this study is to evaluate the effectiveness of applying PRP in the management of tooth extraction sockets determined by histological and immune histochemical examination.…”
Section: Introductionmentioning
confidence: 99%
“…44 Certain pathogens, such as Porphyromonas gingivalis, Tanerella forsythia and Fusobacterium nucleatum, can also influence disease severity. 3 Stress also contributes to increasing the incidence of PD by creating conditions of resistance to glucocorticoids and increased IL-1, IL-6 and TNF-α production, 45 caused by a dysfunction of CD11b monocytes in response to microbial products. 46 Stress leads to down regulation of genes that are activated by glucocorticoids and act to suppress the immunoresponse, while up-regulating genes that cause exacerbation of the inflammatory process, both of which are factors that explain the intimate relationship between stress and PD.…”
Section: Pathophysiology Of Periodontal Diseasementioning
confidence: 99%